PEMBARUAN HUKUM ISLAM MELALUI KONSEP AL-TA’WÎL NASHR HAMID ABU ZAYD - Akh. Syaiful Rijal (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2015)
Abu Zayd reconstruct the concept of texts with linguistic approach (al-manhaj al-tahlîl al-lughawî) in the broadest sense, including hermeneutics and semeotics. For Abu Zayd, ta’wîl different tafsir. He looked ta'wil as productive and objective reading as opposed to talwin, which tendentious reading-ideological (qirâ'ah mughridah aydulûjiyyah). The implications of understanding ta'wil of Abu Zayd are: First, there is something missing in understanding the text of the Qur’an, the awareness of the historicity of religious texts, that he is the text linguistics and that language is a social and cultural product. Second, put the text in the context of the Qur'an as a whole. By doing this Abu Zayd hope that the "unspeakable" (implicit) can be disclosed. Therefore, Abu Zayd borrow distinction adil-dhahir about mabda' (principle), qâ'idah (rules), and hukm (law). Qâ'idah is the derivation of Mabda’ and must not conflict with it. Hukm can not be qâ'idah let alone be mabda'. Hukm is specific events and relative. Third, Abu Zayd suggested to a renewal of Islamic law based on the distinction of adil dhahir.